2016
DOI: 10.1007/s00134-016-4424-2
|View full text |Cite
|
Sign up to set email alerts
|

Statins do not prevent cardiac surgery-associated AKI: is ubiquinone the missing link?

Abstract: Statins have become one of the most commonly prescribed drugs worldwide in the prevention of cardiovascular disease. Most benefits are secondary to inhibition of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA reductase) which lowers low-density lipoprotein cholesterol levels. However, statins also have cholesterolindependent, pleiotropic effects that occur within hours of initiation and include improved endothelial function, anti-apoptotic, anti-inflammatiory, antioxidant, antithrombotic, and immunomodulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Meanwhile, a Cochrane review could not find a benefit of statins on AKI after cardiac surgery (5). Additionally, some studies showed that statins are not renoprotective against AKI after contrast administration following cardiac surgery (6)(7)(8). Likewise, there is a 25-fold increased relative risk of AKI associated with high-dose statins over low-dose statins in patients with congestive heart failure (2).…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Meanwhile, a Cochrane review could not find a benefit of statins on AKI after cardiac surgery (5). Additionally, some studies showed that statins are not renoprotective against AKI after contrast administration following cardiac surgery (6)(7)(8). Likewise, there is a 25-fold increased relative risk of AKI associated with high-dose statins over low-dose statins in patients with congestive heart failure (2).…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…The observed statin-related adverse effect on renal function, however, was unexpected and not explained. This fueled a hypothesis, recently put forward by Schetz and Oudemans-van Straaten, linking the lack of renoprotection to a statin-induced depletion of coenzyme Q10 (CoQ10, aka ubiquinone) (8). CoQ10 is a naturally occurring, lipid-soluble electron carrier which is essential for mitochondrial oxidative phosphorylation and production of adenosine triphosphate (9).…”
mentioning
confidence: 99%